Javardeye: Gaze input for cursor control in a structured editor - Santos, A. L. (2022)
Programmers spend a considerable time jumping through editing positions in the source code, often requiring the use of the mouse and/or arrow keys to position the cursor at the desired editing position. We developed Javardeye, a prototype code editor for Java integrated with eye tracking technology for controlling the editing cursor. Our implementation is based on a structured editor, leveraging on its particular characteristics, and augmenting it with a secondary - latent cursor - controlled by eye gaze. This paper describes the main design decisions and tradeoffs of our approach.